2018
DOI: 10.3390/molecules23061346
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Quantification of Ellagitannins and Related Polyphenols in Geranium thunbergii Using Quantitative NMR

Abstract: Compared to commonly employed liquid chromatography-based methods, quantitative nuclear magnetic resonance (qNMR) is a recently developed method for accurate quantification of natural compounds in extracts. The simultaneous quantification of ellagitannins and the related polyphenols of Geranium thunbergii were studied using qNMR after a short-term and long-term decoction. The qNMR fingerprint for quantifying ellagitannin was presented in this work. Geraniin was observed in the short-term decoction as a major c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…For example, it has been noted that G. macrorrhizum has shown significant hypotensive activity in anesthetized cats [1]. In Japan, G. thunbergii has been approved as an official antidiarrheal drug [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been noted that G. macrorrhizum has shown significant hypotensive activity in anesthetized cats [1]. In Japan, G. thunbergii has been approved as an official antidiarrheal drug [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Campanula species have been reported to contain polyphenols, steroids, phenylpropanoid derivates, triterpenes, and polyacetylenes and show antioxidant activity [30,31]. Previous phytochemical studies on the Geranium genus have shown the presence of phenolic compounds such as gallic, ellagic, quinic acid, quercetin, geraniin, and corilagin [32][33]. Melampyrum arvense has been reported to exhibit antimicrobial and antioxidant activity and contain phenolic compounds [34].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we showed that GN had greater anti-influenza activity than the other constituent compounds of GHE, suggesting that GN was an important active component of GHE. Interestingly, GN is known to be hydrolyzed to corilagin, gallic acid, ellagic acid, and acid after 1 h of decoction 35 . Bastian et al .…”
Section: Discussionmentioning
confidence: 99%